Penguatan Organisasi Pemuda Desa dalam Mempersiapkan 1000 Hari Pertama Kehidupan (HPK) di Padukuhan Garon, Desa Panggungharjo, Kabupaten Bantul - Dody Hartanto; Ratu Matahari; Desi Nurfita (Jurnal Pengabdian Pada Masyarakat, 2021)
STRENGTHENING VILLAGE YOUTH ORGANIZATIONS IN PREPARING FOR THE FIRST 1000 DAYS OF LIFE (HPK) IN PADUKUHAN GARON, PANGGUNGHARJO VILLAGE, BANTUL REGENCY. Bantul Regency is one of 60 priority districts for stunting prevention in Indonesia. The incidence of stunting in Bantul Regency in 2018 was 22.89% and this number was lower than in 2013, namely 26%. Even so, this still makes Bantul Regency one of the areas for stunting in Indonesia. The incidence of stunting will have an impact on the health of the baby which will affect their growth and development. Maternal education and knowledge related to nutrition are important in determining behavior and attitudes to prepare for the first 1000 days of life. Based on this situation, the health conditions and nutritional fulfillment of prospective mothers and mothers before pregnancy and postpartum greatly affect fetal development and the risk of stunting. The aim of this activity is to increase adolescent understanding of the importance of preparing 1000 days of life and skilled solutions to adolescent problems with the approach peer-to-peer case studies. The results of the intervention indicated that the knowledge of the target group regarding adolescent health and nutrition had increased.